Tren Global dalam Model Pembelajaran Sastra: Analisis Bibliometrik Berdasarkan Database Scopus - Syihaabul Hudaa; Muhammad Rohmadi; Raheni Suhita; Edy Suryanto; Luo Ying (ESTETIK : Jurnal Bahasa Indonesia, 2025)
This study is based on the importance of literature education in the development of Indonesian culture within the global cybernetics flow. However, Indonesian literature education, which has gained international interest, faces significant challenges. These challenges include the low appreciation for literature and the difficulty of global access. This study aims to analyze global trends in the model of Indonesian literature education using bibliometric methods based on data from the Scopus database. The analysis aims to understand research patterns and international contributions to the development of literature education models. Through the collection and analysis of metadata from over 900 articles, this study found significant developments in publication numbers, increased international collaboration, and emerging trends since 2015. The results indicate that the use of digital technologies, such as interactive learning applications, is crucial in adapting literature education to the existing global trends.